Macrophage Polarization in the Osteoarthritis Pathogenesis and Treatment - Xiongfei Zou; Hongjun Xu; Wenwei Qian (Orthopaedic Surgery)
ABSTRACT Osteoarthritis (OA) is a prevalent degenerative disorder that severely impacts quality of life due to pain and disability. Although the pathophysiology of OA remains incompletely understood, recent research highlights the role of synovial inflammation in OA onset and progression, driven primarily by inflammatory infiltrates, especially macrophages, in the synovium. These macrophages respond to the local microenvironment, polarizing into either pro‐inflammatory (M1) or anti‐inflammatory (M2) subtypes. This review focuses on the role of macrophage polarization in OA pathogenesis and treatment, emphasizing how M1/M2 polarization is influenced by pathways such as STAT, NF‐κB, caspase, and MAPK. These pathways induce low‐grade inflammation within OA‐affected joints, altering chondrocyte metabolism, inhibiting cartilage repair, and impairing mesenchymal stem cell chondrogenesis, thereby contributing to OA progression. Additionally, this review discusses potential therapies targeting macrophage polarization, encompassing compounds, proteins, cells, and microRNAs, to offer insights into novel treatment strategies for OA.